Accuracy and Ethics, Feelings and Failures: Youth Experimenting with Documentary Practices of Performing Reality - Gallagher, Kathleen; Mealey, Scott; Jacobson, Kelsey (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2018)
For young artists and their educators, the adoption of documentary theatre practices can be deeply appealing given their seemingly privileged capacity to truthfully represent the multi-faceted realities of contemporary life. The often ubiquitous impulse, however, toward straightforward, narrative representations may in fact betray the reality (felt and lived) that young people seek to earnestly convey. This article, drawing on three different examples of youth engagement with documentary and oral history theatre techniques in the cities of Toronto (Canada) and Tainan (Taiwan), explores how young theatre-makers find themselves wrestling with the ethics of unsettling and/or reinforcing the performance and reception of real stories in “the right way.” The authors conclude by advocating for an uncynical praxis of failure that resists well-intentioned, normative performances of past “truths” and makes instead disruptive and often messy space for socio-political, pedagogical, and aesthetic possibilities.